Optical Lithography Patterning of SiO2 Layers for Interface Passivation of Thin Film Solar Cells. Issue 12 (16th September 2018) - Bose, Sourav; Cunha, José M. V.; Suresh, Sunil; De Wild, Jessica; Lopes, Tomás S.; Barbosa, João R. S.; Silva, Ricardo; Borme, Jérôme; Fernandes, Paulo A.; Vermang, Bart; Salomé, Pedro M. P.
Abstract : Ultrathin Cu(In, Ga)Se2 solar cells are a promising way to reduce costs and to increase the electrical performance of thin film solar cells. An optical lithography process that can produce sub‐micrometer contacts in a SiO2 passivation layer at the CIGS rear contact is developed in this work. Furthermore, an optimization of the patterning dimensions reveals constrains over the features sizes. High passivation areas of the rear contact are needed to passivate the CIGS interface so that high performing solar cells can be obtained. However, these dimensions should not be achieved by using long distances between the contacts as they lead to poor electrical performance due to poor carrier extraction. This study expands the choice of passivation materials already known for ultrathin solar cells and its fabrication techniques. Abstract : Interface passivation of ultrathin Cu(In, Ga)Se2 solar cells is important to achieve enhanced performance of solar cells. The potential of SiO2 as a passivation layer and the implementation of nano‐patterning (production of sub‐micrometer contacts) on SiO2 by optical lithography is investigated. Co‐relation between the dimensions of sub‐micrometer contacts and its implications on performance of the ultrathin passivated solar cells is thoroughly investigated.